From Education-to-Work : Opportunities and Challenges in the West Bank and Gaza - Brodmann, Stefanie; Cuadra, Ernesto P.; Allouche, Mohamad Ismail; Hillis, Samira Ahmed (World Bank, Washington, DC, 2012)
Young Palestinians face serious employment challenges upon graduation. In 2009, unemployment among youth 15-24 years old was 28 percent for men and 36 percent for women in West Bank and 57 percent for men and 68 percent for women in Gaza. To better understand the reasons behind these poor labor market indicators, the Ministry of Education and Higher Education (MOEHE) in collaboration with the World Bank conducted focus group discussions with concerned stakeholders in March 2011. This quick note provides a summary of the presentation on the patterns of education-to-work transitions of youth in the West Bank and Gaza (WBG) made by the World Bank team to the focus group meetings. It also incorporates a summary of the subsequent discussions.